Haptic Visuality and Film Narration. Mapping New Women’s Cinema in Spain - Guillamón-Carrasco, Silvia (Communication & Society, 2020)
There is a trend in female film production in the 21st century in the context of Spain towards a type of cinema that we could classify as haptic. It is a mode of representation concerned with multisensory expression in film images. In this article, we shall study this haptic visuality in the works of four filmmakers: Isabel Coixet, Paula Ortiz, Mar Coll and Carla Simón, whose films in this century exemplify the trend. The method chosen is textual analysis, which will provide us with the necessary tools to study matters concerning representation (framing), narration (nuclei and catalysis) and communication (spectatorial subject). These three analytical categories together will enable us to set out the representational parameters of haptic cinema in filmic texts. The results obtained reveal that the elements related to framing (handheld camera usage, grainy images, and the recurrent presence of close-ups) help to express the characters’ subjective, sensory world. As for the narrative model, a prevalence of catalysis and descriptive function can be seen, which helps the characters’ affections and emotions to be widely expressed. Likewise, inferences and ellipsis help weave filmic discourses that involve the audience cognitively, constructing a communicative model that fosters interpretational openness and a kind of interpellation that seeks affective and intellectual communion with the spectatorial subject.